Germ Cell Neoplasms of Sacrococcygeal Region: Clinical Characteristics, Outcomes and Analysis of Recurrence after Treatment; A Comprehensive 20-Year Single Center Study - Samir Hasan; Ülgen Çeltik; Gözde Şakul; Ahmet Çelik; Mustafa Orkan Ergün (Galenos Yayinevi, 2024)
Aim: This study aimed to evaluate the clinical characteristics and outcomes of recurrent sacrococcygeal germ cell tumors (SC-GCTs). Materials and Methods: This study was conducted with patients diagnosed with SC-GCTs between 2002 and 2022. Epidemiology, diagnostic and treatment methods, anatomic/histopathological classifications and recurrence were evaluated. Results: This study included 55 patients (Female/Male: 45/10). According to Altman's-classification, 16 patients (29.1%) were Type I, 14 (25.5%) Type II, 12 (21.8%) Type III and 13 (23.6%) Type IV. Histologically, 69.1% of the lesions were mature teratomas, 14.5% were immature teratomas, and 16.4% were malignant teratomas. Eleven patients developed recurrent sacrococcygeal teratoma (recurrence age: 5 months-12 years). According to Altman's classification, 2/11 patients were Type II, 5/11 patients were Type III, and 4/11 patients were Type IV. The pathological results of the original tumors were mature teratoma in 4/11 patients, immature teratoma in 4/11 patients, and malignant teratoma in 3/11 patients. Malignant relapse with yolk sac tumor was detected in 6/11 patients, mature teratoma in 4/11 patients, and immature teratoma in 1/11 patients. Conclusion: The risk of malignancy increases with age and Altman's Type III and IV. Recurrent tumors may have different histopathological types from the original tumor. The risk of recurrence as a malignant tumor after immature teratomas was higher than mature teratomas.